Hubungan Status Gizi dengan Gangguan Menstruasi pada Remaja Putri di SMA Al-Azhar Surabaya - Riris Novita (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2018)
Background: The period of puberty is an imprtant period in growth and development, especially the reproductive function. Menstrual disorders can be a sign of disease or the presence of abnormal hormonal system. This implies an impaired reproductive function that can affect the reproductive period in adulthood. The causes of abnormality hormonal system in the body can be affected by intake of nutritions in adolescents that can measured by looking at nutritional status.Objectives: The purpose of this research is to analyze correlation between nutritional status and menstrual disorders of female adolescent in SMA Al-Azhar Surabaya.Methods: This reasearch belong analytic observational reasearch with cross sectional design. The populationin this study is high school students in Al-Azhar Surabaya. From calculation by using simple random sampling, obtained 98 students as sample. The process of colecting data is done by interviewing on the assessment of menstrual disorders. Nutritional status was assessed by neasuring height and weight of young women. The classification is based on value of BMI/ age z-score table for 5-19 years old child from WHO. Data analysis was performed by using chi-square test (α=0.05).Results: From the research can be seen that 60.20% of respondents experienced in menstrual disorders. Most of the respondents experienced of menstrual disorders of Premenstrual Syndrome (PMS) and dysmenorrhoea, respectively 30%. In nutritional status, young women with less nutritional status amount 27.55% and more nutritional status is 16,33%. Based on statistical tests conducted, the results obtained that there is significant relation between nutritional status and incidence of menstrual disorders (p=0.035).Conclusion: There is corelation between nutritonal status with menstrual disorders of female adolescent in senior high school Al-Azhar Surabaya.ABSTRAKLatar Belakang: Masa pubertas merupakan masa yang penting dalam pertumbuhan dan perkembangan terutama fungsi reproduksi. Gangguan mentruasi dapat menjadi pertanda adanya penyakit ataupun adanya sistem hormon yang tidak normal. Hal ini berarti fungsi reproduksi terganggu yang dapat berpengaruh terhadap masa reproduksi pada saat dewasa. Penyebab dari ketidaknormalan hormon dalam tubuh dapat dipengaruhi oleh asupan makanan dari remaja yang dapat diukur dengan melihat status gizi.Tujuan: Tujuan dari penelitian ini adalah untuk menganalisi hubungan status gizi dengan gangguan menstruasi pada siswi SMA Al-Azhar SurabayaMetode: Penelitian ini termasuk penelitian observasional analitik dengan rancang bangun potong lintang. Populasi pada penelitian ini adalah siswi SMA Al-Azhar Surabaya. Hasil dari perhitungan simple random sampling didapat 98 siswi sebagai sampel. Pengambilan data dilakukan dengan cara wawancara pada pengkajian gangguan menstruasi. Status gizi dinilai dengan mengukur tinggi badan dan berat badan dari remaja putri. Klasifikasi didasarkan pada nilai tabel z-score IMT/U untuk anak perempuasn usia 5-19 tahun dari WHO. Analisis data dilakukan dengan menggunakan uji chi-square (α=0,05)Hasil: Dari hasil penelitian dapat dilihat bahwa 60,20% responden mengalami gangguan menstruasi. Sebagian besar responden mengalami gangguan menstruasi berupa Premenstrual Syndrom (PMS) dan dismenorea, masing-masing sebesar 30%. Untuk status gizi, masih ada remaja putri yang mempunyai status gizi kurang yaitu 27,55% dan status gizi lebih sebesar 16,33%. Berdasarkan uji statistik yang dilakukan, diperoleh hasil bahwa ada hubungan yang bermakna antara status gizi dengan kejadian gangguan menstruasi (p=0,035).Kesimpulan: Terdapat hubungan antara status gizi dengan gangguan menstruasi pada remaja putri SMA Al-Azhar Surabaya